THE PHILOSOPHICAL AND AESTHETIC FUNCTIONS OF THE IMAGE OF NIGHT IN EASTERN AND WESTERN POETICS (World Conference on Agricultural and Earth Sciences, 2026)
The image of night occupies an important place in both Eastern and Western literary poetics as a universal artistic and philosophical symbol. In literary discourse, night is not only a temporal phenomenon but also a multidimensional aesthetic category associated with loneliness, silence, fear, spiritual contemplation, metaphysical anxiety, and existential consciousness. This article examines the philosophical and aesthetic functions of the image of night through a comparative analysis of Eastern and Western poetic traditions.
Keywords: poetics of night, existentialism, Eastern literature, Western literature, philosophical aesthetics, loneliness, metaphysical contemplation, absurdity, literary symbolism, mythopoetics.